PENGARUH DISIPLIN DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA BAGIAN PEMBIAYAAN PT BANK PERKEDITAN RAKYAT (BPR) AKASIA MAS DI TANGERANG SELATAN - moh. rizki erdiawan; Hamdi Supriadi (Yayasan Sahabat Cendekia Jaya, 2024)
ABSTRACTThe purpose of this study was to determine the effect of discipline and work environment on employee performance of in the financing section of PT Bank Perkreditan Rakyat (BPR) Akasia Mas in South Tangerang. The method used is quantitative. The sampling technique used saturated sampling and obtained a sample as much as 70 respondents. Data analysis using validity, reliability , classical assumption, regression analysis, correlation coefficient, coefficient of determination and hypothesis tests. The results of these study are Discipline has a significant effect on employee performance with a determination coefficient value of 73.9% and the hypothesis test is obtained ttest > t table or (9.039 > 1.995). Work environment has a significant effect on employee performance with a coefficient of determination of 65.1% and the hypothesis test is obtained t count > t table or (7,072 > 1.995). Training and work environment simultaneously have a significant effect on employee performance with the regression equation Y = 5,559 + 0,517X1 + 0,350X2. The coefficient of determination is 61.9% while the remaining 38.1% is influenced by other factors. Hypothesis testing obtained Ftest > F table or (54,504 > 2,740). Keywords: Discipline, Work Environment , Employee Performance